Holiday junctions for the model of dna: Holiday junctions for the model of dna - Xatamov, N.M.; Malikov, N.N.; Mamadjanova, , M.M. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. We consider a DNA molecule as a configuration of the Potts model on paths of the Cayley tree. For this model, we study probability distributions of the Holliday junctions in the DNA molecules with respect to the new translation-invariant Gibbs measures given in [7]. Each such measure describes the state (phase) of a set of DNA molecules